Greener energy for ocean transportation : biofuel - Quek, Pei Yu (Nanyang Technological University, 2021)
With growing environmental concerns, especially with the introduction of IMO 2020 and the Paris Agreement as a means to reduce sulphur emissions and increasing temperature. The maritime industry begins to shift its attention away from using conventional heavy fuel oil (HFO) in sea transportation and focus on greener alternatives to replace HFO. These greener alternatives are more sustainable than HFO and produces lesser emission, thereby meeting regulations placed to control emissions, while working towards IMO 2050 in reducing emissions in shipping by 50%. This project delve into 3 alternative greener fuels that are sustainable and feasibility to be adopted by the maritime industry. This report focuses on the feasibility of biofuel adoption by the maritime industry. Introduction of the global climate is addressed, focusing on the amount of carbon and sulphur emissions produced over the years. Advancement of marine fuels and the emissions produced by the shipping industry is further elaborated. Literature review on biofuel would focuses on the economic, technological and environmental factors of using biofuel, while looking at current usage of biofuel in the maritime industry. Interviews and online perception survey was conducted to gain an overall sentiments of greener fuel adoptions by professionals in the maritime industry, while addressing the difficulties faced. Industry perception gathered through the interviews provided a deeper understanding on how the maritime industry is moving towards the common sustainability goals and the difficulties and challenges faced. Analysis was perform using the results gathered, where Wilcoxon signed ranked test was performed to determine the significance of the survey results. Feasibility of biofuel adoption was addressed using strength, weakness, opportunities and threats faced in biofuel adoption. Recommendations for further research was elaborated with a final conclusion on of biofuel adoption while comparing various fuel adoptions.